Comparative study of anticancer efficacy of aсonitinecontaining agent BC1 against ascite and solid forms of Ehrlich’s carcinoma - Dasyukevich, O.I.; Solyanik, G.I. (Experimental Oncology, 2007)
Aim: To study anticancer activity of аconitine-containing agent BC1 in vivo. Methods: BC1 water solution was administered per os to mice bearing ascite or solid form of Ehrlich’s carcinoma. Anticancer effect of BC1 administered per os was evaluated by the indexes of tumor growth inhibition and average life span of experimental animals. Results: BC1 didn’t show anticancer activity in the case of ascite form of Ehrlich’s carcinoma. At the same time treatment with BC1 resulted in 77.3% growth inhibition of solid form of Ehrlich’s carcinoma (p < 0.05). Conclusion: BC1 is active in vivo against tumor with angiogenesis-dependent growth.